Efforts to Improve Chemistry Learning Outcomes Through the Problem Posing Learning Model in Class X Tkr 1 SMK Negeri 2 Palembang - Nova Astriani; Muhammad Hadeli L; Rahma Aini (Pedagogy Review, 2023)
Abstract: Efforts To Improve Chemical Learning Outcomes Through Problem Posing Learning Model In Class X Tkr 1 of SMK Negeri 2 Palembang. This classroom action research aims to improve students' chemistry learning result of Class X TKR 1 SMK Negeri 2 Palembang through Problem Posing learning model. The study was conducted in two cycles, each cycle consisting of two meetings. The data were obtained by using observation sheet and test instrument of student learning result which was done at the end of the meeting. Improvement of student learning outcomes can be seen from the average of student learning outcomes before the action done (T0) of 64.97 with mastery learning 33.33%, an increase in cycle I (T1) to 66.01 with mastery learning 45.45% and in cycle II (T2) increased to 79,5 with learning mastery 84,84%.Keywords: classroom action research, problem posing model, student chemistry learning result